Effects of Simvastatin Beyond Dyslipidemia: Exploring Its Antinociceptive Action in an Animal Model of Complex Regional Pain Syndrome-Type I - Vieira, Graziela; Cavalli, Juliana; Gonçalves, Elaine C. D.; Gonçalves, Tainara R.; Laurindo, Larissa R.; Cola, Maíra; Dutra, Rafael C. (Frontiers in Pharmacology, 2017)
Simvastatin is a lipid-lowering agent that blocks the production of cholesterol through inhibition of 3-hydroxy-methyl-glutaryl coenzyme A (HMG-CoA) reductase. In addition, recent evidence has suggested its anti-inflammatory and antinociceptive actions during inflammatory and pain disorders. Herein, we investigated the effects of simvastatin in an animal model of complex regional pain syndrome-type I, and its underlying mechanisms. Chronic post-ischemia pain (CPIP) was induced by ischemia and reperfusion (IR) injury of the left hind paw. Our findings showed that simvastatin inhibited mechanical hyperalgesia induced by CPIP model in single and repeated treatment schedules, respectively; however simvastatin did not alter inflammatory signs during CPIP model. The mechanisms underlying those actions are related to modulation of transient receptor potential (TRP) channels, especially TRMP8. Moreover, simvastatin oral treatment was able to reduce the nociception induced by acidified saline (an acid-sensing ion channels (ASICs) activator) and bradykinin (BK) stimulus, but not by TRPA1, TRPV1 or prostaglandin-E2 (PGE2). Relevantly, the antinociceptive effects of simvastatin did not seem to be associated with modulation of the descending pain circuits, especially noradrenergic, serotoninergic and dopaminergic systems. These results indicate that simvastatin consistently inhibits mechanical hyperalgesia during neuropathic and inflammatory disorders, possibly by modulating the ascending pain signalling (TRPM8/ASIC/BK pathways expressed in the primary sensory neuron). Thus, simvastatin open-up new standpoint in the development of innovative analgesic drugs for treatment of persistent pain, including CRPS-I.